Língua e identidade de jovens imigrantes: crianças que cruzaram fronteiras Japão - Brasil - Uchigasaki, Ruchia (Universidade Federal de São Carlos, 2025)
This thesis investigates the relationship between language and identity among young Japanese-Brazilians who grew up in transit between Japan and Brazil, experiencing multilingual contexts throughout their childhood and adolescence. In this sense, the general objective of the research is to analyze, based on the narratives of the collaborators, how the experience with plurilingual linguistic practices influenced their life trajectories and the construction of their identities. In order to achieve this objective, the research is based on the following guiding questions: (1) how were the linguistic environment and (self)recognition in the two languages (Portuguese/Japanese) configured by the collaborators in a situation of mobility between Japan and Brazil?; (2) what relationships can be established between living in a plurilingual environment and/or mobility and the choice of academic and professional path?; (3) how do the experiences of mobility and contact with different languages relate to the identity constitution of these subjects? The theoretical basis is based on the approaches to plurilingual linguistic competence by Coste, Moore and Zarate (2009), the theory of situated learning by Lave and Wenger (1991), the conceptions of relative and variable identity proposed by Block (2007) and Norton (2013), as well as the concept of “children who cross borders” by Kawakami (2010). This is therefore a qualitative, interpretivist study which uses narrative research methodology, focusing on life history and lived experience, prioritizing understanding and the construction of meanings based on the participants' accounts. The results indicate that the collaborators had partial, complementary, unbalanced and dynamic plurilingual skills, which were manifested through strategic communicative practices in everyday life. The language experiences in Portuguese and Japanese enabled them to become aware of their own language skills, which was strongly linked to how they were perceived by others in different social contexts. This perception directly influenced the use and learning of languages, as well as decisions related to university education, career choice and the development of life projects. Therefore, the analysis shows that the subjects construct their identities in constant negotiation with the cultural and linguistic contexts in which they are inserted, demonstrating that mobility and plurilingualism play a fundamental role in the constitution of the self in the present and in the projection of the future.
Language and identity of young immigrants: children who crossed borders Japan - Brazil
Lengua e identidad de los jóvenes inmigrantes: niños que cruzaron fronteras Japón - Brasil
Keywords: Competência plurilíngue; Identidade; Mobilidade e trânsito; Narrativas de vida; Jovens nipo-brasileiros; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA